2003
DOI: 10.1097/00005131-200303000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Knee Dislocations: Where Are the Lesions?

Abstract: This study showed a wide variety of injury patterns. Knees had to have at least two ligaments injured to be dislocatable but not necessarily both cruciate ligaments. Sports injuries have the same pattern of injury as motor vehicle accidents, suggesting similar forces of injury. The study demonstrates a high incidence of reattachable avulsion injuries to ligaments and soft tissues in dislocatable knees. These may not be as easily dealt with if surgery is delayed beyond 3-4 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(53 citation statements)
references
References 15 publications
5
44
0
4
Order By: Relevance
“…Other studies with smaller cohorts reported a mean age of 28 to 32 years. 1,10,33 Meniscal injuries were found in 37.3% of patients in the current study, and cartilage injuries were found in 28.3%. Richter et al 26 reported a lower incidence (15%) of meniscal injuries in association with knee dislocation, while Krych et al 17 reported higher rates of meniscal and chondral lesions associated with knee dislocation in 121 patients (122 knees), with 76% of patients having a meniscal or chondral injury (55% with meniscal tears, 48% with chondral injury).…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Other studies with smaller cohorts reported a mean age of 28 to 32 years. 1,10,33 Meniscal injuries were found in 37.3% of patients in the current study, and cartilage injuries were found in 28.3%. Richter et al 26 reported a lower incidence (15%) of meniscal injuries in association with knee dislocation, while Krych et al 17 reported higher rates of meniscal and chondral lesions associated with knee dislocation in 121 patients (122 knees), with 76% of patients having a meniscal or chondral injury (55% with meniscal tears, 48% with chondral injury).…”
Section: Discussionmentioning
confidence: 43%
“…3,4,28,29,33 Most studies are retrospective in nature, and few patients are included. The incidence of these injuries is reported to be between 0.02% and 0.2% of all orthopaedic injuries.…”
mentioning
confidence: 99%
“…Neurological compromise associated with KD occurs most commonly to the common peroneal nerve [26] and has a reported incidence of between 10-40% [27-29]. One study by Peskun et al performed univarate and multivariate regression analysis to suggest that the risk of peroneal nerve injury is increased in those patients with a higher BMI (p = 0.0206), associated fibular head fracture (p = 0.009) or associated vascular injury (p = 0.035) [26].…”
Section: Acute Managementmentioning
confidence: 99%
“…Traumatic dislocation of the tibiofemoral joint is considered to be rare in Europe and western civilized countries[1,2], but when present it often has dramatic social and economic consequences for the patient[3-9]. Spontaneous reduction makes the true frequency of knee dislocation unclear.…”
Section: Introductionmentioning
confidence: 99%